Mathematics Courses for the Seventh Year and Eighth Year, 1978 Reprint - New York State Education Dept., Albany. Bureau of General Education Curriculum Development; New York State Education Dept., Albany. Bureau of General Education Curriculum Development; State Univ. of New York, Albany ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
Scope and content charts specifying units, topics, and time allotment are provided for grades 7 and 8. Units covered in grade 7 are sets, systems of numeration, whole numbers, positive rational numbers, geometry, and ratio, proportion, and percent. Units covered in grade 8 are sets, real numbers, ratio, proportion and percent, geometry, coordinate geometry, and statistics. Suggestions to teachers are given for each unit. (MP)
ERIC Note: Not available in hard copy due to marginal legibility of original document.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum; Curriculum Guides; Geometry; Grade 7.; Grade 8.; Number Concepts; Secondary Education; Secondary School Mathematics; Set Theory; Guides, Classroom -- Teacher